Heterosis in papaya: inter and intragroup analysis - Deisy Lúcia Cardoso; Lucas Nunes da Luz; Celia Maria Peixoto de Macêdo; Leandro Gonçalves Simões Azeredo; Messias Gonzaga Pereira (Revista Brasileira de Fruticultura, 2014)
Papaya (Carica papaya L.) is a typical crop of tropical areas, and Brazil is one of the leading world producers. In recent decades, papaya culture has expanded to different regions of the country, but the number of cultivars available is still limited. In the present study, a complete diallel cross was carried out using eight accessions of papaya from the UENF/Caliman germplasm bank. Four genotypes belong to the Formosa heterotic group and four, to the Solo group. This study aimed to evaluate the occurrence and viability of exploring heterosis in heterotic intragroup hybrids. Fifty-six hybrid progenies were generated and evaluated. Among the Formosa intragroup hybrids, two hybrid combinations (MR x J4 and MR x SK) showed heterosis for all traits, as well as good average total fruit production. Among the Solo intragroup hybrids, three hybrid combinations (WM x GG, WM x SS and WM x SM) stand out for fruit production and high content of soluble solids. In Formosa x Solo hybrids, all hybrid combinations with the parent JS (JS x WM, JS x GG, JS x SS and JS x SM) showed high fruit quality and good average for fruit production. The heterotic profile of the hybrids tested allowed the identification of promising hybrids within Formosa and Solo heterotic groups. The analysis of the canonical variables also allowed the visualization of distinct groups of hybrids, depending on the provenance of the parents.